2017
DOI: 10.3390/molecules22060862
|View full text |Cite
|
Sign up to set email alerts
|

Daucosterol Inhibits the Proliferation, Migration, and Invasion of Hepatocellular Carcinoma Cells via Wnt/β-Catenin Signaling

Abstract: Hepatocellular carcinoma (HCC) is one of the leading causes of cancer-related death worldwide. The purpose of this study was to determine the effects of daucosterol on HCC by investigating Wnt/β-catenin signaling. In this study, HepG2 and SMMC-7721 cells were treated with varying concentrations of daucosterol, and the corresponding inhibitory effects on HCC cells were examined via CCK-8 assays. Cell migration and invasion abilities were detected via transwell assays. β-Catenin and phospho (p)-β-catenin levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 46 publications
1
26
0
1
Order By: Relevance
“…The KEGG pathway analysis revealed that the MAPK and Wnt signaling pathways are potentially correlated with the regulation of the four candidate miRNAs. As reported, the MAPK and Wnt signaling pathways were all associated with proliferation, migration, invasion and prognosis and HCC ( 44 48 ). Consequently, we hypothesized that PVT1 plays a vital role in HCC by regulating the expression of the four miRNAs via the MAPK or Wnt signaling pathways, which requires further investigation on the precise molecular mechanism of PVT1 in HCC.…”
Section: Discussionsupporting
confidence: 54%
“…The KEGG pathway analysis revealed that the MAPK and Wnt signaling pathways are potentially correlated with the regulation of the four candidate miRNAs. As reported, the MAPK and Wnt signaling pathways were all associated with proliferation, migration, invasion and prognosis and HCC ( 44 48 ). Consequently, we hypothesized that PVT1 plays a vital role in HCC by regulating the expression of the four miRNAs via the MAPK or Wnt signaling pathways, which requires further investigation on the precise molecular mechanism of PVT1 in HCC.…”
Section: Discussionsupporting
confidence: 54%
“…Upon binding to the receptor, Wnt induces a cascade of intracellular signaling events containing a major component, Glycogen Synthase Kinase-3 (GSK-3), which mediates β-catenin phosphorylation, leading to its degradation via ubiquitin/proteasome pathway [ 23 ]. SB-216763 is a selective GSK-3 inhibitor, which has been demonstrated to inhibit the Wnt/β-catenin signaling pathway [ 24 ]. In our study, it was observed that the inhibitory effects of pirfenidone on cell growth and on the expression and phosphorylation of β-catenin were abolished by SB-216763 exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Daucosterol might act as its structural analogue daucosterol linoleate which was demonstrated to inhibit tumor growth and tumor weight at 100 mg/ kg in MCF-7 xenograft nude mice model, by activating the intrinsic caspase-dependent apoptosis 39. Additionally, many scientific reports have demonstrated and discussed the potential of daucosterol to trigger apoptosis through the caspase signaling pathway in various cell lines, including breast cancer cells [20][21][22][23]40. Furthermore, some authors showed that daucosterol (IC50 9.77 μg/mL) as well as daucosterol linoleate (IC 50 53.27 μg/mL) induced their cytotoxic effects in MCF-7 breast cancer cells through the intrinsic pathway of apoptosis.…”
mentioning
confidence: 99%